HIV-1 epidemiology and circulating subtypes in the countryside of South Brazil - Carina Sperotto Librelotto; Tiago Gräf; Daniel Simon; Sabrina Esteves Matos de Almeida; Vagner Ricardo Lunge (Revista da Sociedade Brasileira de Medicina Tropical, 2015)
INTRODUCTION: Human immunodeficiency virus type 1 (HIV-1) has spread worldwide, with several subtypes and circulating recombinant forms. Brazil has an incidence of 20.5 HIV-1/acquired immunodeficiency syndrome (AIDS) patients per 100,000 inhabitants; however, the Southernmost State of Rio Grande do Sul (RS) has more than twice the number of HIV-1-infected people (41.3/100,000 inhabitants) and a different pattern of subtype frequencies, as previously reported in studies conducted in the capital (Porto Alegre) and its metropolitan region. This study examined HIV-1/AIDS epidemiological and molecular aspects in the countryside of Rio Grande do Sul. METHODS: Socio-demographic, clinical and risk behavioral characteristics were obtained from HIV-1-positive adult patients using a structured questionnaire. HIV-1 subtypes were determined by nested-polymerase chain reaction (PCR) and sequencing of the pol and env genes. RESULTS: The study sample included 149 (55% women) patients with a mean age of 41.8 ± 11.9 years. Most (73.8%) patients had a low education level and reported heterosexual practices as the most (91.9%) probable transmission route. HIV-1 subtypes were detected in 26 patients: 18 (69.2%) infected with subtype C, six (23.1%) infected with subtype B and two (7.7%) infected with BC recombinant forms. CONCLUSIONS: These data highlight the increasing number of HIV-1 subtype C infections in the countryside of South Brazil.